Assessment of Pig Production and Constraints in Mecha District, Amhara Region, Northwestern Ethiopia - Yeshambel Mekuriaw; Bimrew Asmare (Advances in Agriculture, 2014)
The study was undertaken in Mecha District, Amhara National Regional State, Northwestern Ethiopia, in 2012/2013. The objectives of the study were to assess production purpose and management practices of pig and to identify constraints and generate baseline information for further research and development. From the district, 6 Kebeles (name of local administration in Ethiopia) were identified and from each Kebele 15 households were selected making the number of respondents 90. A pretested semistructured questionnaire was employed for collecting data through interview and face to face discussion with the pig owners including key informant group discussion and secondary sources. Multivisits to study sites were also made to observe the feeding, housing, and other pig management practices. The results indicated that the purpose of pig production is mainly targeted for additional income and profit for the household in which pigs are sold for external markets as pork is not consumed by local community. Results indicate that pig keepers were farmers or nonfarmers with small land holding and people engaged in other types of work. The major feed source for pig was grazing, followed by crop residue feeding and supplementing with household and agricultural by-products. Pigs are kept in house at least for the night, though the pig house was not separated by age or physiological stage. The most important constraints of pig production in the study area were feed shortage, poor access to veterinary services, and poor market linkage.